Front Cover: Crystal Structure and Characterization of Two Layered Copper(II) Coordination Polymers with Anions of 3‐Phosphonopropionic Acid and (RS)‐2‐Phosphonobutyric Acid (Z. Anorg. Allg. Chem. 4/2018) - Köferstein, Roberto; Arnold, Michael; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2018)
The cover picture shows sections of the two layered coordination polymers Cu[µ3‐O3P(CH2)2COOH]·2H2O (1) and Cu[(RS)‐µ3‐O3PCH(C2H5)COOH]·3H2O (2) obtained from aqueous solution with Cu2+ and anions of 3‐phosphonopropionic acid and (RS)‐2‐phosphonobutyric acid, respectively. The layers are confined in both cases by COOH groups pointing to the interlayer space. Thus these coordination polymers can be regarded as the protonated form of a weakly acidic cation exchanger with layer‐like structure. The negative charge density of the deprotonated layers would be similar to that known from layered silicates. A weak antiferromagnetic interaction is observed at low temperature in both compounds obviously caused by super‐superexchange paths between copper cations. More details are discussed in the article by R. Köferstein, M. Arnold, and C. Robl on page 205 ff.